The deacetylation reaction in Eucalyptus wood: Kinetics and effects on the effective diffusion - Inalbon, Maria Cristina (2009)
The removal of native acetyl groups from hardwood O-acetyl-glucuronoxylan has a strong effect on physical characteristics, accessibility and structure of this polymer. The removal also has effects on the swelling and ion transport capacity of the cell wall of hardwoods. In this work, a kinetic expression for Eucalyptus wood deacetylation is determined. Two liquid mediums are considered: a simple alkaline one and another with a higher sodium concentration. The kinetic expression is a power law for the acetyl content and the concentrations in the liquid medium dependence, and is an Arrhenius type expression for temperature dependence. The kinetic expression can be useful to predict the physical properties of wood since the analysis of deacetylation effects on effective capillarity (ECCSA) shows that the acetyl content is a determining factor of wood ionic transport capacity